The gut ileal mucosal virome is disturbed in patients with Crohn’s disease and exacerbates intestinal inflammation in mice - Cao, Zhirui; Fan, Dejun; Sun, Yang; Huang, Ziyu; Li, Yue; Su, Runping; Zhang, Feng; Li, Qing; Yang, Hongju; Zhang, Fen; Miao, Yinglei; Lan, Ping; et al. (Nature communications, 2024)
Gut bacteriome dysbiosis is known to be implicated in the pathogenesis of inflammatory bowel disease (IBD). Crohn’s disease (CD) is an IBD subtype with extensive mucosal inflammation, yet the mucosal virome, an empirical modulator of the bacteriome and mucosal immunity, remains largely unclear regarding its composition and role. Here, we exploited trans-cohort CD patients and healthy individuals to compositionally and functionally investigate the small bowel (terminal ileum) virome and bacteriome. The CD ileal virome was characterised by an under-representation of both lytic and temperate bacteriophages (especially those targeting bacterial pathogens), particularly in patients with flare-up. Meanwhile, the virome-bacteriome ecology in CD ileal mucosa was featured by a lack of Bifidobacterium - and Lachnospiraceae-led mutualistic interactions between bacteria and bacteriophages; surprisingly it was more pronounced in CD remission than flare-up, underlining the refractory and recurrent nature of mucosal inflammation in CD. Lastly, we substantiated that ileal virions from CD patients causally exacerbated intestinal inflammation in IBD mouse models, by reshaping a gut virome-bacteriome ecology preceding intestinal inflammation (microbial trigger) and augmenting microbial sensing/defence pathways in the intestine cells (host response). Altogether, our results highlight the significance of mucosal virome in CD pathogenesis and importance of mucosal virome restoration in CD therapeutics. Gut bacteriome dysbiosis has been implicated in the pathogenesis of inflammatory bowel disease (IBD). Here, they authors characterize the small bowel (terminal ileum) virome and bacteriome of patients with Crohn´s Disease (CD), and show that ileal virions from CD patients causally exacerbate intestinal inflammation in IBD mouse models.